PROFIL PEMBUDIDAYA RUMPUT LAUT DI PULAU TERLUAR INDONESIA (STUDI KASUS: DESA LUANG BARAT, KABUPATEN MALUKU BARAT DAYA) - Gayus Engelbertus Hayer; Wardis Girsang; Ivonne Raystika Gretha Kaya; Manuel Kaya; Astaman Amir (Universitas Pattimura, 2022)
Seaweed farming at Indonesian outer island generally done with traditional technique. Limitedless about information and market access is the main problem of the seaweed farming. Luang Barat, Mdona Hyera Distric is one of village that located at Indonesian outer island. This research aims to figured about seaweed farming and profile about the farmers. Method are used is survey method with sampling technique is observation and questionare to 44 respondent. Seaweed farming done personal by all farmers and it help by family members. Generally the age of all farmers is 30-39 years old with latest education at primary school and average of family member is 5 person. Besides seaweed farming, almost all farmers had a another job like as a government staff at the village, made a traditional boat and as a trader.